Numerical Study on the Thermal Hydraulic Characteristics in a Wire-Wrapped Assembly of LFRs - Li, Jun; Fang, Di; Guo, Chao; Wang, Mingjun; Deng, Jian; Tian, Wenxi; Qiu, Suizheng; Su, G. H. (Frontiers in Energy Research, 2020)
The concept of wire-wrapped assembly has been widely adopted in liquid metal-cooled reactors to enhance the capability of flow and heat transfer. The detailed 3D thermal hydraulic behaviors of liquid metal in the wire-wrapped assembly directly affect the safety of the reactor. In the present work, a numerical study on a 19-pin wire-wrapped assembly cooled by a lead-bismuth eutectic was carried out using the CFD method. The geometrical model is referred to in the test section in KIT’s 19-pin experiments, which is a scaled test assembly based on the MYRRHA reactor. The established CFD model was validated against experimental data and results showed that the SST k-ω model accompanied with the modified Prt was appropriate for the current problem. Then the numerical models were extensively used in the modeling of the blocked assembly flow with a cylindrical blockage. Also, the influences of blockage longitude, position, and porosity on the thermal hydraulic characteristics in the assembly were evaluated in detail. This work is meaningful for the deep understanding of safety features under the condition of assembly blockage operation in LFRs.